Prediction of mental well-being and general health based on body image mediating self-compassion in female athletes - Kabiri Aq Ziarat, Shadi; Taheri, Afsaneh; Abolmaali Alhosseini, Khadijeh (Applied Family Therapy Journal (AFTJ), 2023)
Aim: The purpose of this research was to predict mental well-being and general health based on body image with the mediation of self-compassion in female athletes in Tehran. Methods: This was a descriptive correlational study that was conducted using the structural equation method. Also, in terms of the purpose, this study was practical. The statistical population of this research was all female athletes who referred to sports clubs in Tehran city. 250 people were selected by the convenience sampling method. The participants used a link to Keyes et al.’s mental well-being questionnaire (2003), Goldberg’s general health questionnaire (1979), Neff et al.’s self-compassion questionnaire (2003), and body image questionnaire (Brun et al., 1990). Data were analyzed using descriptive analysis, Spearman’s correlation, and path analysis using SPSS and PLS software. Results: The results showed that body image has a direct effect on general health (β=-0.22; P=0.004), and self-compassion (β=-0.21; P=0.010). Also, self-compassion has a direct effect on mental well-being (β=0.32; P<0.001). The indirect effect of body image on mental well-being was confirmed through the mediation of self-compassion (β=0.07; P=0.035). Conclusion: According to the results, it can be concluded that strategies that increase self-compassion can provide a better picture of body image and increase the mental well-being of female athletes.